O ACD/CHEMSKETCH® COMO APOIO À APRENDIZAGEM DE CONCEITOS QUÍMICOS - Mendes Mortate, Daniela; Rodrigues Borges, Luz Clarita; Ribeiro Mamede Luiz, Maraisa; Bosso Tomal, Adriana Aparecida (Intercursos, 2026)
não há